Engine Control Unit for a 4 cylinder motorcycle engine - Ríkarður Ragnarsson 1992- (2017)
An Engine control unit (ECU) is a component found in all modern vehicles. In the case of a competition vehicle, the variety of ECUs decrease massively. especially if the vehicle is constructed for the purpose of competing in an international competition, because of various rules and regulations regarding the vehicle that limit the choice of an ECU. In such competition vehicles, the ECUs are generally built for universal purposes but maintaining the performance quality of a competition ECUs. These types of ECUs are usually expensive. The project of this thesis is designing and building an ECU for a 4 cylinder motorcycle engine. The ECU will be used by the Formula Student team of Reykjavík University and the goal is to create a simple ECU to decrease both the cost and the complexity. The process includes programming, circuit designing, and PCB making. The hardware and firmware designs are then tested. Vélartölva er búnaður sem allar nútíma bifreiðar innihalda. Ef um er að ræða sérsmíði bíls, getur val á vélatölvu verið flókið ferli. Sérstaklega ef bíllinn er smíðaður í þeim tilgangi að keppa eigi á honum í alþjóðlegri keppni þar sem taka þarf mark á ýmsum reglum sem takmarka valmöguleika. Í slíkum keppnisbílum eru yfirleitt notaðar tölvur sem eru hannaðar sem alhliða tölvur í sem flestar gerðir keppnistækja. Þær gerðir tölva eru yfirleitt ansi dýrar. Verkefni snýst um að hanna og smíða vélartölvu fyrir 4 sílindra vél úr mótorhjóli sem notuð verður í keppnisbíl Formula Student lið Háskóla Reykjavíkur. Markmiðið verkefnisins er að smíða einfalda vélatölvu til að minnka bæði kostnað og flækjustig. Ferlið felst í því að forrita, hanna rafrásir og búa til prentplötu. Hönnun rása og forrits er síðan prófuð.